Study on public perception on the effectiveness of herbal treatment as alternative treatment by sudents of Diploma in Public Administration / Jacinta Franky ...[et.al.] - Franky, Jacinta; Sinde, Mono (2002)
Herbs are a type of neglected weed that has been made into natural medicine since thousands of years ago by our ancestor. Herbal medications have been used thousands of years ago and in these modern days that herbal treatment has been commercialized to cater for the modern people. Herbal medicine was said to have some impressive credential that cannot be substituted by any other modern medicine. Nowadays, herbal medication has evolved from its traditional form that is from plant used naturally to clinical pills that are produced in the laboratories. The natural form of herbal medication has changed gradually causing in some cases the user will experience side effects that can lead to death. This study is done in order to have an in depth look into the way the peoples in the study area practice herbal medication. In spite of having some knowledge about herbs from published books or articles, the respondents' still practice ancient ways of preparing herbal medicine as that way have been practiced long within their family. The reason of herbal treatment being practiced varies according to the need of the respondents themselves. Among the reasons are to cure abdominal discomfort, to relieve pain and to promote good health.